2017
DOI: 10.1002/hed.24683
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers in metastatic cutaneous squamous cell carcinoma of the head and neck

Abstract: Low total lymph node ratio is associated with improved outcomes in node-positive head and neck cutaneous SCC. © 2017 Wiley Periodicals, Inc. Head Neck 39: 772-778, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 32 publications
12
50
0
Order By: Relevance
“…ENE was an exceedingly common feature, occurring in 77% of our cohort. This is consistent with previous literature on metastatic nodal cSCCHN from large series in Australia and New Zealand, with the incidence of ENE ranging between 57% and 85% . As a result of the high rates of ENE, application of AJCC8 nodal classification criteria resulted in 77% patients being upstaged.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ENE was an exceedingly common feature, occurring in 77% of our cohort. This is consistent with previous literature on metastatic nodal cSCCHN from large series in Australia and New Zealand, with the incidence of ENE ranging between 57% and 85% . As a result of the high rates of ENE, application of AJCC8 nodal classification criteria resulted in 77% patients being upstaged.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous literature on metastatic nodal cSCCHN from large series in Australia and New Zealand, with the incidence of ENE ranging between 57% and 85%. 11,[23][24][25] As a result of the high rates of ENE, application of AJCC8 nodal classification criteria resulted in 77% patients being upstaged. The majority of patients diagnosed as AJCC7 N1 were upstaged to AJCC8 N2a, and the majority of patients with AJCC7 N2 or N3 disease were upstaged to the new AJCC8 N3b classification.…”
Section: Discussionmentioning
confidence: 99%
“…found an LNR >0.21 was an independent predictor of disease progression and reduced survival in their cohort of 238 patients, but did not analyse the number of nodal metastases. In another retrospective study of 149 patients, Hirshoren et al . found both the LNR and the number of metastatic lymph nodes predicted reduced overall survival on multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…The LNR expresses the ratio of involved lymph nodes to the total number of lymph nodes removed and has become a well‐recognized prognostic factor in many cancer types. Several studies have suggested the LNR is also an independent prognostic factor in metastatic cSCCHN . Tseros et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation